Contribution of Parkia biglobosa to the feeding value of pasture systems in West Africa - Sabiiti, E.N.; Cobbina, J.; Lambourne, J. (New Zealand Grassland Association, 1993)
Parkia (Parkia biglobosa) is an important traditional economic tree legume with several uses for the rural farmers in West Africa, although it has received only limited research. Parkia is dominant in natural pastures or fallow fields that are used for livestock grazing. The tree provides shade to forage grass and livestock, protects soil from heat and torrential tropical rains, resists fire damage and coppices very well after defoliation. Farmers grow several food crops under the canopy. The fruits, leaves and young seedlings, which are highly rutitions, form an important fodder for livestock in the dry season when natural pastures are poor in quality. Tree fodder production potential is quite high. The seeds and leaves contain up to 30 and 18 percent crude protein, respectively, and seeds are also eaten by humans as a major source of protein. The genus has a potential for nitrogen fixation. The paper presents data on fodder quality of Parkia and how it should be managed properly for integration in silvipastoral systems of West Africa.